MODERATION AND MAINSTREAM OF PESANTREN OR MADRASAH EDUCATION - Ahdar; Abdul Halik; Musyarif (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
Pesantren and Madrasah were born because of the acculturation of local culture and Islam, so Islamic education practitioners should be open, adaptive, and not anti-cultural. The principle that should be followed is to preserve the old values ??or traditions that are still good and take on new values ??or traditions that are better. That way, Islamic education will advance and modern, but not uprooted from its historical roots. The method used is a library method that focuses on the study of reference books that discuss the education of Islamic boarding schools and madrassas. The purpose of this paper is to be able to understand the meaning of pesantran / madrasa education in particular in Indonesia Cottage. Islamic boarding schools have gone through various periods of time, this shows that this Islamic educational institution shows a strong survival. This resilience was born because of the existence of idealism and consistency in the progress of his struggle. Supposedly, idealistic values ??such as the sincerity of the kiai and his sincere commitment to maintaining and developing Islamic teachings can be used as a foothold of idealism for educational practitioners today. The goal is to make educational institutions and activities a place for commercialization and politicization, to reap profits and power.